Polypropylene/red mud polymer composites: Effects of powder size on friction and wear behaviors - (:unkn) unknown (Metal Powder Industries Federation, 2017)
Polymer/clay composites have received great attention in the past three decades owing to their light weight coupled with significantly better mechanical and barrier properties than the corresponding neat polymer resins. An investigation was carried out on the effects of red mud powder size and ratio on the friction and wear properties of polypropylene /red mud polymer composites. Red mud, in four different concentrations (0, 10, 20 and 30 wt %) and three different powder size (180, 63 and 38 micron) were added to PP to produce composites. The friction properties, including the dynamic and static friction, and the wear properties of the composites were investigated. The structure of the composites were investigated by scanning electron microscopy and compared to friction and wear properties as a function of red mud powder content and size. © 2017 Metal Powder Industries Federation. All Rights Reserved.